Analisis Perbandingan Aplikasi Data Mining Dalam Memprediksi Kualitas Kinerja Karyawan Menggunakan Metode Algoritma C4.5 - Hijrah Hijrah; Maulidar Maulidar; Adria Adria (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
This study was conducted to measure and compare the values ​​of accuracy, precision, and recall, from the rapid miner and weka data mining applications by comparing the value of the confusion matrix, the application of the confusion matrix method was carried out by testing the training data obtained from the performance data of company employees engaged in the Internet. Service Providers. Testing the data is carried out to predict the quality of employee performance with the C4.5 algorithm. The approach taken in this research is carried out with a qualitative approach and uses library research research techniques, the results of which are analyzed using the analytical method of comparing the results of the confusion matrix value. From the results of the comparative analysis that has been carried out, the results of the rapid miner application are superior in terms of Accuracy of 94.12% and Recall of 95.6%, while the Weka application is better only in terms of Recall by 95.6%. The test was carried out using the rapid miner data mining application version 7.6.0.0.1 and the Weka application version 3.8.1.